(untitled) (LINGUISTICA, 2015)
This thesis deals with the type of illocutionary acts on Liz Gilbert™s dialogue in Eat Pray Love movie. The objectives of the study were to describe the types of illocutionary acts used by Liz Gilbert in Eat Pray Love movie, the dominant type of illocutionary acts used by Liz Gilbert in Eat Pray Love movie and the reason why the dominant type of illocutionary acts occur on Liz Gilbert™s dialogue in Eat Pray Love movie. This research was conducted by using descriptive qualitative design. Descriptive qualitative research is descriptive in that the researcher is interested in the process of meaning and understanding gained through words or picture (Hancock 2007:7). This research used descriptive qualitative research because the intention of this study was to describe how illocutionary used in the movie.The data were the transcript of Liz Gilbert™s dialogue. The findings showed that there were 466 utterances which contained five types of illocutionary acts, namely: Representatives 198 utterances (42.49%), Directives 169 utterances (36.27%), Expressives 89 utterances (19.10%), Commisives 9 utterances (1.93%) and Declarations 1 utterance (0.21%). The most dominant type of illocutionary act was Representatives with total number 198 utterances (42.49%) because Liz Gilbert as the main character often described and informed about the situation of her journey and experience when she visited Italy, India and Indonesia where she finally found the balance of life, true love and happiness.